Effect of Heat Treatment on the Corrosion Behavior of Mg-10Gd Alloy in 0.5% NaCl Solution - Silva Campos, Maria del Rosario; Blawert, Carsten; Mendis, Chamini L.; Mohedano, Marta; Zimmermann, Tristan; Proefrock, Daniel; Zheludkevich, Mikhail L.; Kainer, Karl Ulrich (Frontiers in Materials, 2020)
In 0.5 wt. % NaCl aqueous solution, Mg-10Gd alloy shows promising corrosion resistance. The microstructure of this alloy was modified via heat treatments to understand the effect of accompanying microstructural changes on the corrosion resistance. It was found that corrosion performance depends both on the amount and the distribution of the cathodic intermetallic phases. The T4 heat treatment (24 h at 540°C) caused the Gd to distribute uniformly in the matrix, which had positive effect on corrosion resistance showing a delay in the time required for the first observation of localised corrosion. The T4 heat treated specimens, specimens aged at 200°C and 300°C, showed relatively uniform degradation and thus these heat treatments are not detrimental in terms of corrosion resistance. In contrast, heat treatment at 400°C seems to increase the formation of small cuboidal particles rich in Gd, most likely to be GdH2 particles, in the matrix, resulting in a detrimental effect on the corrosion behaviour.